2018
DOI: 10.4028/www.scientific.net/amm.877.33
|View full text |Cite
|
Sign up to set email alerts
|

Mesoporous Iron-Manganese Magnetic Bimetal Oxide for Efficient Removal of Cr(VI) from Synthetic Aqueous Solution

Abstract: A facile co-precipitation method was established for synthesis of mesoporous iron-manganese magnetic bimetal oxide (MIMO) and its adsorption property was studied for removal of toxic metal ion hexavalent chromium from aqueous solution. XRD pattern of MIMO confirms the existence of Fe2O3 and Mn3O4 particle, out of which Mn3O4 is ferrimagnetic in nature. Synthesized MIMO has shown high saturation magnetization (23.08 emu/g), high BET surface area (178.27 m2/g) and high pore volume (0.484 cm3/g), which makes it a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…From the time of contact, it can be concluded that the absorption rate initially increased and then equilibrated (Wu et al 2019). Due to a larger number of active sites, the structure and area of the adsorbent are faster in the early times and allow heavy metal to penetrate to a large extent (Bhowmik et al 2018;Davarnejad et al 2018). Other researchers reported similar results for adsorption of chromium by different adsorbents (Theydan 2018;Jamshidifard et al 2019;Li et al 2019).…”
Section: Effect Of Contact Timementioning
confidence: 74%
“…From the time of contact, it can be concluded that the absorption rate initially increased and then equilibrated (Wu et al 2019). Due to a larger number of active sites, the structure and area of the adsorbent are faster in the early times and allow heavy metal to penetrate to a large extent (Bhowmik et al 2018;Davarnejad et al 2018). Other researchers reported similar results for adsorption of chromium by different adsorbents (Theydan 2018;Jamshidifard et al 2019;Li et al 2019).…”
Section: Effect Of Contact Timementioning
confidence: 74%
“…In recent decades, almost 10-15 % of dyes from dyeing process units have entered the aquatic environment through industrial waste. [1] Organic dyes are colored compounds that are widely used in the manufacture of textiles, leather, paints, clothing, rubber, biological imaging, plastic paper making, food processing, etc. The side effects of this dye liquid waste are environmental problems, including decreased water quality, damage to soil productivity, and health problems in the environment around polluted areas.…”
Section: Introductionmentioning
confidence: 99%
“…Typically, such a process necessitates the use of a large volume of chemical reagents, or reductants. An alternative method of recovery that does not require the use of reagents is the galvanocoagulation method [7][8][9][10][11][12]. The ecological advantage of this approach is the possibility of joint disposal of various metalworking wastes or other industries [13].…”
Section: Introductionmentioning
confidence: 99%